DAKWAAN BATAL DEMI HUKUM SETELAH PEMERIKSAAN POKOK PERKARA DALAM SIDANG PENGADILAN (Studi Putusan Nomor 19/Pid.Sus/2015/PN.Sim) - Anggara Suryanagara; Alvi Syahrin; Muhammad Hamdan; Jelly Leviza (USU LAW JOURNAL, 2016)
ABSTRACT It is very interesting to analyze when a summons was legally annulled by the judge after substance of the case was examined and indictment was read and it is stated as the last decision. The problems of the research were as follows: first, why the judge handed down the verdict which stated that the summons was legally annulled and the examination of the substance of the case and the indictment was related to the prevailing legal provisions; and secondly, whether the summons which was legally annulled in the Verdict No. 19/Pid.Sus/2015/PN.Sim could be summoned before the court when it is related to the principle of ne bis in idem. The judge’s verdict which stated that the summons was legally annulled after the examination of the substance off the case and the indictment in the Verdict No. 19/Pid.Sus/2015/PN.Sim was based on the explanation that the indictment was inaccurate, unclear, and incomplete. The person, Rikal, in the summons was not presented, no action was done, and he was listed in the Man Wanted List. Besides that, each person’s role was not explained. The amount of money received by Rikal was not in line with the fact in the proceedings. According to the legal provisions, the judge’s verdict was contrary to the principle of Justice and brought about legal uncertainty in the abrogation of the summons. The abrogation of the summons is bound to the principle of ne bis in idem since the subject of the case had been examined and the indictment had been read so that the verdict was categorized as acquittal and the principle of ne bis in dem was bound which indicated that the prosecutor could not file the case to be examined, indicted, and tried twice; it could only be appealed to the Supreme Court. It is recommended that Article 156, paragraph 2, Article 143, paragraph 2 letter b, and Article 191, paragraph 2 of the Criminal Code be interpreted widely, acquittal is not only related to a criminal case but also the summons is inaccurate, incomplete, and unclear, and the prosecutor appeal the case to the Supreme Court and not to the Higher Court.   Keywords :               Summons, Indictment is legally Annulled, Examination of the Subject of the Case, Principle of Ne bis in Idem